DETECTION OF SOMACLONAL VARIATIONS AMONG MICROPROPAGATED POPULATION OF SOME IMPORTANT MEDICINAL PLANTS - Tiwari, S.; Jatav, D. S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Demand of healthy medicinal planting material in India and international drug market is increasing continually, while, many important medicinal plants have been declared endangered due to less seed viability, low germination percent and vegetative propagation also susceptible for disease. Plant tissue culture has come up as an alternative of poor natural germination of seed and vegetative propagation which provides desired number genetically uniform pest free plants in a short span of time. One of the major problems of in vitro plant cultivation is the high incidence of somaclonal variation. The RAPD analysis was carried out to assess genetic relationship among micropropagated population the basis of scoring of band exhibited by amplified products using NTSYS_pc. RAPD and ISSR marker were used to assess clonal fidelity of medicinal plants viz., Chlorophytum borivilianum, Bacopa monnieri, Rauwolfia serpentina and Oroxylum indicum. Initial screening for somaclonal variation on the basis of morphological traits was carried out starting second month of culture. Among six to eighth month old cultures <0.3% phenotypic variation were observed, however, upon ISSR and RAPD analysis such variants proved to be genetically true to the parental type. During 9-12 months, ISSR and RAPD analysis revealed 10 to 24 percent dissimilarity to the parental type among 0.5% observed phenotypic variations.